2021
DOI: 10.3390/pharmaceutics13122122
|View full text |Cite
|
Sign up to set email alerts
|

An Atlas of the Quantitative Protein Expression of Anti-Epileptic-Drug Transporters, Metabolizing Enzymes and Tight Junctions at the Blood–Brain Barrier in Epileptic Patients

Abstract: The purpose of the present study was to quantitatively elucidate the levels of protein expression of anti-epileptic-drug (AED) transporters, metabolizing enzymes and tight junction molecules at the blood–brain barrier (BBB) in the focal site of epilepsy patients using accurate SWATH (sequential window acquisition of all theoretical fragment ion spectra) proteomics. Brain capillaries were isolated from focal sites in six epilepsy patients and five normal brains; tryptic digests were produced and subjected to SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…In a study done with bone marrow-derived macrophages, LPS-induced resistance to DEX treatment was attributed to a 7-fold increase in GRβ mRNA levels in these cells [34], which could explain the resistance to DEX-mediated claudin-5 increase in HBMEC+HA-GRβ or EPI-ECs in our study. Interestingly, a recent study has also found that claudin-5 expression was significantly decreased 1.97-fold in epileptic brain microvessels compared to controls, but occludin expression was not significantly different between the two groups [35]. This supporting evidence further confirms that the decrease in tight junction proteins in the epileptic brain region may not afflict all types of tight junction proteins, and we describe here for the first time that GRβ may play a role in that phenomenon.…”
Section: Discussionsupporting
confidence: 89%
“…In a study done with bone marrow-derived macrophages, LPS-induced resistance to DEX treatment was attributed to a 7-fold increase in GRβ mRNA levels in these cells [34], which could explain the resistance to DEX-mediated claudin-5 increase in HBMEC+HA-GRβ or EPI-ECs in our study. Interestingly, a recent study has also found that claudin-5 expression was significantly decreased 1.97-fold in epileptic brain microvessels compared to controls, but occludin expression was not significantly different between the two groups [35]. This supporting evidence further confirms that the decrease in tight junction proteins in the epileptic brain region may not afflict all types of tight junction proteins, and we describe here for the first time that GRβ may play a role in that phenomenon.…”
Section: Discussionsupporting
confidence: 89%
“…Here, we applied previously developed sensitive liquid chromatography with tandem mass spectrometry (LC-MS/MS)-based quantitative targeted absolute proteomics (QTAP) methods [28,29]. The LC-MS/MS-based QTAP approach enables a sensitive and robust quantitative analysis of low abundant target proteins with multiple advantages over the antibody-based methods such as western blotting [30], and has been extensively applied for protein expression quantification of transporters and other proteins in the NVU in health and diseases [17,28,29,[31][32][33][34][35]. Moreover, we compared the alterations in transporter protein expression in the isolated brain microvessels and brain prefrontal cortices of 5xFAD mice to previously published data in AD patients and other animal models in order to assess the relevance of the animal models to mimic AD-related changes in transporter protein expression in the NVU in humans.…”
Section: Introductionmentioning
confidence: 99%
“…However, some other brain disorders are also characterized by P‐gp upregulation 19,20 . Moreover, recent proteomic analyses suggest the P‐gp is globally underexpressed and not overexpressed in the epileptogenic human brain 21,22 . Likewise, key tight junction proteins are downregulated in the epileptogenic brain, 22,23 supporting looser rather than tighter barrier than in the healthy brain.…”
Section: Marketed Asms Are Smaller Than Other Cns Drugsmentioning
confidence: 99%
“… 19 , 20 Moreover, recent proteomic analyses suggest the P‐gp is globally underexpressed and not overexpressed in the epileptogenic human brain. 21 , 22 Likewise, key tight junction proteins are downregulated in the epileptogenic brain, 22 , 23 supporting looser rather than tighter barrier than in the healthy brain. Alternatively, seizures might theoretically alter the porosity of endothelial cell membranes, thereby slowing down or preventing drug “jumping” through transitory holes in the membrane.…”
Section: Marketed Asms Are Smaller Than Other ...mentioning
confidence: 99%